DROUGHT RISK EFFECTS ON LIVELIHOODS OF RURAL COMMUNITIES IN CHIPINGE SOUTH, ZIMBABWE - Witness Mutero & Clemance. J. Mutekwa (International Journal of Research Science and Management, 2018)
The study assessed effects of drought risk on the livelihoods of rural communities in Chipinge South, Zimbabwe. It explored their main sources of livelihood and how drought shapes their lives either negatively or positively. Furthermore, the studylooked at efforts by government, Non-Governmental Organisations (NGOs) and Community-Based organisations (CBOs), in providing services and goods to the community, and how they have been a stumbling block to the efforts. On the other hand, the study evaluated whether food aid promoted livelihood strategies to cope with drought risk. The research adopted a mixed method approach, which included quantitative and qualitative techniques. It administered structured questionnaires to a random sample of 110 households in the study area. The study discovered that effects of drought risks directly affect sources of livelihoods of most households in Chipinge South. Most households depend on farming as their major source of livelihood, and the bulk of them fail to harvest as a direct result of drought. The study recommends development of the area in aspects such as rural electrification, service provision, irrigation, infrastructure, and decentralising vital services. This can improve the conditions in the community and allow for diversification of the sources of livelihood.